(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Background. Corneal ulcers are a major cause of visual impairment and blindness, particularly in developing regions. While hospitalization is often necessary for severe cases, the factors influencing prolonged hospital stays remain inadequately explored. Identifying key sociodemographic and clinical predictors can aid in optimizing patient management and resource allocation. Objective. This study aims to assess the sociodemographic and clinical factors associated with prolonged hospitalization in patients with corneal ulcers. Methods. A retrospective observational study was conducted over one year with a sample size of 200 hospitalized patients diagnosed with corneal ulcers. Data were collected on sociodemographic variables (age, gender, socioeconomic status, rural vs. urban Residence) and clinical characteristics (ulcer size, depth, microbial aetiology, hypopyon presence, diabetes, immunosuppression, prior ocular surgery, treatment delay, and need for surgical Intervention). Length of hospital stay was categorized as prolonged vs. non-prolonged, and statistical analyses, including multivariate regression, were performed to identify independent predictors. Results. Prolonged hospitalization was significantly associated with larger ulcer size (p < 0.01), fungal aetiology (p < 0.05), presence of hypopyon (p < 0.01), delayed treatment (p < 0.01), and diabetes mellitus (p < 0.05). Patients with fungal ulcers had higher complication rates and required extended inpatient care. Rural patients experienced delayed diagnosis and referral, contributing to longer hospital stays. Multivariate analysis confirmed that microbial aetiology, ulcer severity, and systemic comorbidities were independent predictors of prolonged hospitalization. Conclusion. Early diagnosis and prompt treatment are critical in reducing hospitalization duration and improving outcomes in corneal ulcer patients. Strengthening primary eye care services, community-based screening, and outpatient follow-up can mitigate the burden of prolonged hospitalization. Further multicenter studies and prospective trials are warranted to validate these findings and explore innovative treatment approaches.